Market sales prospecting by analyzing customer buying pattern using machine learning - Ahmed, Tanjil; Rahman, Salman; Routh, Niloy; Nirob, Eftakhar Alam (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.